PENGATURAN ASAS OPORTUNITAS DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Darma Santosa, I Kadek; Rai Yuliartini, Ni Putu; Sudika Mangku, Dewa Gede (Jurnal Pendidikan Kewarganegaraan Undiksha, 2021)
This research aim to (1) know and analyze arrangement of opportunity principle in article 35 letter c Act of number 16/2004 about concerning the Prosecutor’s Republic of Indonesia, and (2) know and analyze what is the consideration of public interest as a basis for the basic application of opportunality by the Attorney General. The type of research used is normative legal research. The data is obtained from this research is secondary data, obtained through library research, and analyzed by qualitative juridicial method with the statue approach, conceptual approach, case approach, comparative approach, and historical approach. This research led to the showed that the (1) basic arrangements of opportunity principle are reflected in article 35 letter c Act of number 16/2004 about concerning the Prosecutor’s Republic of Indonesia, but doesn’t clearly determine the parametes of what is meant of public interest, (2) In formulation he public interest based on article explanation 35 letter c are too broad and there are no obvious parameters, so that many interpretations related to the phrase of public interest.